2022
DOI: 10.21511/ppm.20(2).2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and forecasting of Ukraine’s financial security: Choice of alternatives

Abstract: Financial security of a country is an integral part of its economic security and the basis of national security. The paper aims to assess and forecast the level of Ukraine’s financial security using two methodological approaches (the existing one and the authors’ elaboration) to choose the best alternative. The first one is based on the Methodology of the Ministry of Economy of Ukraine. The alternative one has been developed as a multiplicative model of non-linear convolution of relevant direct and indirect im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…determinants), because it establishes the obligation to determine the positive and negative environmental aspects of any development, not only their voluntary recognition [11]. Only in this way can one obtain knowledge-as it seems-where the ecological effectiveness of changes in the development of each organization ends [3][4][5][15][16][17].…”
Section: These Essences Of Research 21 Achievementsmentioning
confidence: 99%
“…determinants), because it establishes the obligation to determine the positive and negative environmental aspects of any development, not only their voluntary recognition [11]. Only in this way can one obtain knowledge-as it seems-where the ecological effectiveness of changes in the development of each organization ends [3][4][5][15][16][17].…”
Section: These Essences Of Research 21 Achievementsmentioning
confidence: 99%
“…In view of this, it is necessary to analyse which indicators are proposed to be calculated by different researchers (Table 2). Compiled by the author on the basis of (Pronoza et al, 2022;Hrynyuk et al, 2021;Franchuk et al, 2020;Kvasnytska et al, 2019;Fedorushchenko et al, 2021;Poltorak et al, 2021;Sylkin et al, 2018;Rekunenko et al, 2022;De Goede, 2021;Shkolnyk et al, 2019) .…”
Section: Reice | 144mentioning
confidence: 99%
“…One of the key links in this process is the analysis and assessment of the level of financial security of an enterprise (FSE). Determining the level of financial security of an institution is still an open problem at the national level, which leads to scientific research on the optimal methodological approach to determining the level of FSB (Hrynyuk et al, 2021;Rekunenko et al, 2022;Tkachuk et al, 2022), which will provide an overall picture of the state of protection of the financial interests of the institution.…”
Section: Introductionmentioning
confidence: 99%
“…Public administration practice has established that economic security is a qualitative parameter of the economic system, which is manifested in the ability to ensure an adequate standard of living based on the adequacy of the resource base for the reproductive processes development and the state's functions. Economic security of the state is the basis of its financial security, including tax [2][3][4][5][6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessing indicators of regression statistics, in particular, R 2 , it was found that constructed models of variables sufficiently determine the variable B at the significance level of 0.5 and reliability of 0.95. Fisher's coefficient indicates a high degree of built models' adequacy in terms of economic performance of the studied countries.…”
Section: Figure 1 Dynamics Of Planned State Tax Revenues Fulfillment ...mentioning
confidence: 99%